The Genotype and Phenotype Features in a Large Chinese MFN2 Mutation Cohort - Ma, Yan; Sun, Aping; Zhang, Yingshuang; Fan, Dongsheng; Liu, Xiaoxuan (Frontiers in Neurology, 2021)
Introduction: Charcot-Marie-Tooth disease type 2A (CMT2A) is a group of clinically and genetically heterogeneous disorders, which is mostly caused by mutations of the mitofusin 2 (MFN2) gene. As the genotype-phenotype characteristics of CMT2A were still incompletely understood, we further explored the spectrum of CMT2A variants in China and demonstrated their phenotypic diversities. Methods: A total of 402 index patients/families with CMT throughout Mainland China were enrolled in this study. Among them, we analysis 20 unrelated index cases with CMT2A by Sanger sequencing, next-generation sequencing or whole-exome sequencing. Detailed clinical and genetic features of CMT2A patients were collected and analyzed. Of note de novo mutations were not rare in MFN2 gene, we compared the clinical features of patients from de novo group with those from non-de novo group. Results: We identified 20 MFN2 variants, which occupying 5.0% of CMT. Most patients presented with early onset and moderate phenotype with abnormal gait and foot drop as the main complaints at onset. Pyramidal signs accounts for 31.6% (6/19) in all patients, which is not uncommon. Four novel variants (p.Tyr752*, c.475-2A>G, p.Val99Met and p.Arg275_Gln276insArg) were identified in the cohort. Besides, de novo variants occupied 35.0%(7/20) in our study with a much earlier age at onset compared with those in the non-de novo group (p=0.021).. Conclusion: Chinese CMT2A is predominant typical pure CMT2A, with early onset and mild to moderate phenotype. Given the high frequency of de novo MFN2 mutations, genetic study should be considered for patients with early onset and severe idiopathic axonal neuropathy.